Late medieval glazed painted wares from Messenia and the question of local pottery production - Konstantinidou, Alexandra (Journal of Greek Archaeology, 2023)
It is commonly asserted that the fragmentation of the Byzantine Empire after the Fourth Crusade in 1204 brought about major political and socio-economic changes that caused the ‘decentralisation’ of ceramic production. However, such abrupt transformations did not usually have an immediate and profound impact on all aspects of everyday life and material culture. In fact, the very concept of ‘centralisation’ in middle Byzantine pottery production is somewhat ambiguous, since it has been based on the production and distribution of glazed ceramics rather than the operation of the workshops themselves. Relying mainly on the glazed ceramics is a problematic practice, since they are usually found in considerably smaller quantities than the plain wares. Furthermore, it has been proven that in the middle Byzantine period (especially in the 12th century) various pottery workshops used different clay sources to produce glazed wares, which shared common technical, typological and decorative features representing a ceramic koine. Some of these wares survived well into the 13th century while at the same time new, ‘hastily’ made, glazed ceramics emerged gradually. These ‘newcomers’ have been often perceived as indicators of multiple new workshops rather than the updated products of existing workshops. This idea, though, is contradicted by the results of recent investigations. Thus, Yangaki correctly concluded that instead of insisting on the concept of ‘decentralisation’ we should first scrutinise the new 13th century wares and evaluate the information that they carry.